Image representations of the body: an analysis in the Google Images search engine (Research, Society and Development, 2021)
Objective: To analyze the imagery representation of the body on the internet. Methodology: With an exploratory-descriptive nature and a quali-quantitative approach, Semiotic Analysis was adopted, based on the theoretical assumptions of Bauer and Gaskell, respecting the methodological stages suggested by the authors: Choice of images; Denotative inventory; Analysis of the levels of meaning. In the first stage, the first 100 images from Google Images were collected, in a cross-section, on December 27, 2020, using the keyword: body. After applying the exclusion criteria, 42 images were selected. Results: The difference between the incidence of genders was significant, with males being present in 14.2% (n = 6) of the images and females in 85.8% (n = 36). According to the morphological profile of the sample, two images classified as out of the stereotyped pattern were identified, while the other photos (95.3%) referred to bodies that fit the stereotyped pattern, that is, that follow the media model of thinness. Still, seeking to identify the representation of the images, the emphasis given to aesthetics is highlighted (n = 31), to the detriment of images related to health (n = 7). Final considerations: The imagery representation of the virtual media presented in the sample shows the desired body as that predominantly female. In addition to the predominance of one gender, this body has specific morphological characteristics, and among women it is related to thinness and among men to a muscular body.